Mutant swarms of a totivirus-like entities are present in the red macroalga Chondrus crispus and have been partially transferred to the nuclear genome - Rousvoal, Sylvie; Bouyer, Betty; López-Cristoffanini, Camilo; Boyen, Catherine; Collén, Jonas (Journal of Phycology, 2016)
International audience Chondrus crispus Stackhouse (Gigartinales) is a red seaweed found on North Atlantic rocky shores. Electrophoresis of RNA extracts showed a prominent band with a size of around 6,000 bp. Sequencing of the band revealed several sequences with similarity to totiviruses, double-stranded RNA viruses that normally infect fungi. This virus-like entity was named CcV. It should probably be regarded as an extreme viral quasispecies or a mutant swarm since low identity (<65%) was found between sequences. Totiviruses typically code for two genes: one capsid gene (gag) and one RNA-dependent RNA polymerase gene (pol) with a pseudoknot structure between the genes. Both the genes and the intergenic structures were found in the CcV sequences. A non-identical gag gene was also found in the nuclear genome of C. crispus, with associated EST and upstream regulatory features. The gene was presumably horizontally transferred from the virus to the alga. Similar dsRNA bands were seen in extracts from different life cycle stages of C. crispus and from all geographical locations tested. In addition, similar bands were also observed in RNA extractions from other red algae; however, the significance of this apparently widespread phenomenon is unknown. No phenotype caused by the infection nor any virus particles, or capsid proteins were identified; thus, the presence of viral particles has not been validated. These findings increase the known host range of totiviruses to include marine red algae.